Konsep Hijab dalam Al-Quran Menurut Surat Al Ahzab Ayat 59 : (Studi Komparatif Ibnu Katsir dan Wahbah Zuhaili) - Izzatur Rifdah Ismail; Zaim Rais (At-Ta'wil: Jurnal Pengkajian al-Qur'an dan at-Turats, 2024)
This article attempts to present another perspective on the interpretation of the hijab concept in verse 59 of Surah Al-Ahzab. The interpretation of the hijab concept is further elaborated by classical exegetes such as Imam Ibn Kathir and contemporary exegete Imam Wahbah al-Zuhayli. This paper aims to compare the interpretation of the hijab concept in terms of its purpose, the reason for the revelation of the hijab law, the manner of its use, and the limitations of the hijab. The method used is library research utilizing primary data from Tafsir Quranul ‘Azhim and Tafsir Ibn Kathir. The research findings indicate the similarity in the meaning of hijab and the purpose of hijab according to Ibn Kathir and Wahbah al-Zuhayli, which is a head covering placed over a veil. (khimar). The purpose of the hijab is mandated or obligatory so that Muslim women are protected from the disturbances of wicked people or those with bad intentions. As for their differences, they lie in the limits of the hijab and the manner of its usage. Imam Ibn Kathir does not require covering the entire face, whereas Wahbah al-Zuhayli requires covering the entire face and prohibits wearing transparent clothing.